PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN PADA GOLDEN SUPERMARKET MANADO - Poluan, Juwita Elisabeth; Areros, William Agustinus; Punuindoong, Aneke (Sam Ratulangi University, 2017)
ABSTRAK. Given the number of malls and supermarkets (supermarket) which is located in the same area, then by itself would give birth to the fierce competition to seize visitors and buyers. Additionally the competition also came from some retailers in traditional markets and shops are scattered in the same area. Golden Supermarkets is one of the famous retail among some retail in the city of Manado. In the motion of daily operations, Golden Supermarkets as shopping centers provide a variety of different goods with different types, brands and sizes at varying price levels. Problem formulation, Based on the background outlined above, then the problem is: What is the quality of services that includes Tangible, Realibility, Responsiveness, Assurance, and Empathy effect on customer satisfaction in the Golden Supermarket Manado.Objective, while the objectives of this research is to determine how much the quality of the services provided by Golden Supermarket.